Exchange Rates and Macro News in Emerging Markets - Guglielmo Maria Caporale; Fabio Spagnolo; Nicola Spagnolo (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper uses a VAR-GARCH(1,1) model to analyse mean and volatility spillovers between macro news (in the form of newspaper headlines) and the exchange rates vis-avis both the US dollar and the euro of the currencies of a group of emerging countries including the Czech Republic, Hungary, Indonesia, Korea, Mexico, Poland, South Africa, Thailand and Turkey over the period 02/1/2003-23/9/2014. The results suggest limited dynamic linkages between the first moments compared to the second moments, causality-in-variance being found in a number of cases. The conditional correlations also provide evidence of co-movement. Finally, the recent global financial crisis appears to have had a significant impact.
Keywords: C32; F36; G15; 330; emerging markets; exchange rates; GARCH model; macro news